SOCIAL TRANSFORMATION OF OLYMPISM FROM THE POSITION OF HISTORICAL ANALYSIS - Peredelsky, A.A.; Mamedov, Azer Agabala oglu; Kortunov, V.V.; Kotusov, D.V.; Zaitsev, A.A. (Theory and Practice of Physical Culture, 2023)
Methods and structure of the study. In the course of the experimental work, an analysis of theoretical sources was carried out and a generalization of the scientific literature on the history of Olympism was carried out. Results and conclusions. Like the movement of humanism, Olympism should by no means be described unequivocally as a socially homogeneous democratic movement. In different eras, Olympism, manifesting itself as a social institution, fulfilled and continues to fulfill fundamentally different social class orders.